Air traffic management and systems II : selected papers of the 4th ENRI International Workshop, 2015 (Springer, 2017)
This book is a compilation of selected papers from the 4th ENRI International Workshop on ATM/CNS (EIWAC2015). The work focuses on novel techniques for aviation infrastructure in air traffic management (ATM) and communications, navigation, surveillance, and informatics (CNSI) domains. The contents make valuable contributions to academic researchers, engineers in the industry, and regulators of aviation authorities. As well, readers will encounter new ideas for realizing a more efficient and safer aviation system.
3.1 Problem Statement.
Keywords: Air traffic control -- Congresses.; Electronics in navigation -- Congresses.; elektronické knihy; electronic books